The virtual environments potential for postgraduate education - Jaqueline García Rodríguez; Reynaldo Fernando Hernández Zayas (Medisur)
Although non-face-to-face education has antecedents dating back to the last century, the COVID-19 pandemic undoubtedly get overcrowded training processes in virtual environments. Education was forced to return in their footsteps. The ways of teaching were rethought; The way of learning was verified in line with contextual demands. The adaptation of learning models transcended the classroom space and gave rise to innovative activities on digital platforms, for students of all educational levels. Four years later, they continue to be implemented, although, particularly in higher medical education, the pace of expansion slows down and their employment is reduced once the degree is achieved. Virtual learning environments are not constrained to the undergraduate level and harbor potential for postgraduate studies, even finding legal support in current resolutions. This article presents some considerations about the potential of virtual environments to develop continuous improvement processes in ubiquitous scenarios. The redesign of undergraduate activities must have continuity in the postgraduate course, as a path of permanent, flexible and open training.